THE EFFECT OF A TRANSFORMATIONAL LEADERSHIP STYLE ON WORK ENGAGEMENT WITH WORK SATISFACTION AS INTERVENING VARIABLES IN K3PG - Ayu Listya Anggraini; Muhammad Rosyihuddin; Eva Desembrianita (Media Mahardhika, 2021)
This study aims to analyze the effect of transformational leadership style and work satisfaction on work engagement. The population used in this study were 109 employees of the Petrokimia Gresik Family Employee Cooperative. The sampling technique used was purposive sampling with the criteria working period of at least 5 years, so the number of samples used was 80 people. The analysis model used is path analysis using SPSS. The research results show that: There is a positive and significant effect of transformational leadership style on work engagement, transformational leadership has positif effect on on work satisfaction, positive and significant effect of work satisfaction on work engagement, and There is a positive influence and significant transformational leadership style on work engagement through work satisfaction. Its indicated that the leaders should be consistent in applying transformational leadership styles and increase employee work satisfaction to increase work engagement for their employees. When employees have work engagement, they will become productive at work so they can make the best contribution to the company.